Muscarinic Receptor Subtypes Mediating Positive and Negative Inotropy in the Developing Chick Ventricle - Hideaki Nouchi; Seri Kaeriyama; Akiko Muramatsu; Masumi Sato; Kunihiko Hirose; Nagako Shimizu; Hikaru Tanaka; Koki Shigenobu (Elsevier, 2007)
The inotropic response to muscarinic receptor stimulation of isolated chick ventricular myocardium was examined at various developmental stages, and the receptor subtype involved was pharmacologically characterized. In embryonic chick ventricles, carbachol (CCh) produced positive inotropy at micromolar concentrations. In hatched chick ventricles, CCh produced negative inotropy at nanomolar concentrations. Neither positive nor negative inotropy was observed in the 19 - 21-day-old embryos. Both positive and negative inotropy were also observed with acetylcholine and oxotremoline-M. The CCh-induced positive inotropy in 7 - 9-day-old embryonic ventricles and the negative inotropy in 1 - 3-day-old hatched chick ventricles were antagonized by muscarinic receptor antagonists; pA2 values for the positive and negative responses of pirenzepine were 7.5 and 7.2, those of AF-DX116 (11-[(2-[(diethylamino)methyl]-1-piperidinyl)acetyl]-5,11-dihydro-6H-pyrido[2,3-b][1,4] benzodiazepine-6-one) were 6.8 and 6.9, those of 4-diphenylacetoxy-N-methylpiperidine (4-DAMP) were 9.0 and 8.5, and those of himbacine were 7.0 and 8.0, respectively. CCh had no effect on action potential configuration. In conclusion, the positive inotropy is most likely mediated by muscarinic M1 receptors and the negative inotropy is mostly likely mediated by muscarinic M4 receptors. Keywords:: carbachol, chick, ventricle, muscarinic receptor, contractile force